From open to robotic surgery in pediatric ureteral reimplantation: overcoming the learning curve for improved outcomes - Mattioli, G.; Fanti, F.; Carlucci, M.; Parodi, S.; Fiorenza, V. (Frontiers in Surgery, 2025)
IntroductionWith growing role of minimally invasive surgery, laparoscopic ureteral reimplantation (LUR) and robotic ureteral reimplantation (RALUR) have gained popularity in pediatric vesicoureteral reflux (VUR) treatment. However, literature on complex ureterovesical junction (UVJ) pathologies remains limited. This study reports RALUR outcomes over time and compares them with those of LUR and open ureteral reimplantation (OUR) for UVJ pathologies at a tertiary center.Materials and methodsData from 80 RALUR (18 non dismembered ND-RALUR and 62 dismembered D-RALUR) performed in 2018–2023 were prospectively collected and compared with data from 21 LUR (16 non dismembered ND-LUR and 5 dismembered D-LUR) in 2018–2020 and 61 OUR in 2014–2021. Surgical indications included VUR, obstructive megaureter (OM), and refluxing obstructive megaureter (ROM), even in duplex system, bladder diverticula, ureterocele and prior UVJ surgeries.ResultsMedian age and weight were 2.1 years, 12 kg (OUR), 1.7 years, 13.5 kg (LUR), and 3.3 years, 15.0 kg (RALUR). No intraoperative complications occurred. Abdominal drainage and bladder catheterization were more frequent and lasted longer in OUR than in RALUR (p < 0.001). RALUR was associated with shorter hospitalization and reduced analgesic use (p < 0.001). Success rates were 79% (OUR), 50% (LUR), and 65% (RALUR), improving to 97%, 95%, and 98% after reinterventions. RALUR success increased from 55% (2020–2021) to 81% (2022–2023) (p = 0.02).DiscussionRALUR achieved comparable success to OUR and LUR while offering improved ergonomics, useful for complex cases, shorter hospital stays, and easier future endoscopic approaches. The increasing success rate reflects the robotic learning curve and growing surgical expertise.